PGPR in Managing Root Rot Disease and Enhancing Growth in Mandarin (Citrus reticulata Blanco.) Seedlings - B N Chakraborty (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2016)
Decline in general plant-health and fruit production in mandarin influenced by abiotic and biotic factors is a major threat to cultivars grown in Darjeeling and Sikkim hills. Fusarium root rot, caused by F. oxysporum, is one of the most serious diseases afflicted during early plant growth stage in Citrus. To address this, seven PGPR isolates - Pseudomonas poae (RMK03), Bacillus stratosphericus (RHS/CL-01), Ochrobactrum anthropi, Paenibacillus lentimorbus, Bacillus pumilus, Bacillus megaterium and Bacillus amyloliquefaciens were isolated from the rhizosphere of Citrus reticulata, C. limonia and Camellia sinensis, and used for evaluating their effect on growth of mandarin seedlings. Pseudomonas poae showed in vitro antagonism to Fusarium oxysporum. Better growth enhancement was noticed with P. poae, B. stratosphericus, O. anthropi and B. pumilus. Enhanced activity of chlorophyll, total protein, phenol, four major defense enzymeschitinase, β-1, 3-glucanase, peroxidase and phenyalanine ammonia lyase was observed upon application of PGPR. P. poae also suppressed root rot caused by Fusarium oxysporum. Use of PGPR, which promote growth besides reducing disease severity to some extent, may lead to use of eco-friendly approaches for controlling plant diseases.